Essential Oil Content and Composition of the Spathe in Some Date Palm (Phoenix dactylifera L.) Varieties in Iran. Issue 2 (3rd March 2020) - Atghaei, Masoomehsoheila; Sefidkon, Fatemeh; Darini, Ali; Sadeghzadeh Hemayati, Saeed; Abdossi, Vahid
Abstract: Phoenix dactylifera L., is a monocotyledonous tree belonging to the family Arecaceae or Palmaceae. In Iranian traditional medicines, the distilled water from the date palm spathe is used as tonic, sedative and calmative herbal medicine. In this study, for the first time, the essential oil content and composition of spathe from seven date palm varieties, Phoenix dactylifera L. (var. Mozafati) (male and female trees), Zahedi, Hallilehie, Piarom, and Keroot, Mordasangh, Medjool) growing in Bam, South of Iran, were determined by means of gas chromatography (GC) and gas chromatography/mass spectrometry (GC/MS) analyses. The results showed a significant difference between the weight of spathe per tree, essential oil percentage and essential oil yield of different varieties at P< 0.01. Comparison of mean values showed the highest essential oil percentage (0.21 %, 0.20 % and 0.15 %) were obtained from Piarom, Zahedi and Mozafati varieties, respectively. Seventeen compounds were identified in the essential oils with 3, 4-dimethoxy toluene (55.2-70.7 %), p-methyl anisol (4.5-28.5 %) and 2, 6-dimethoxy toluene (9.0-19.9 %) as main components. These compounds have anti-paroxysm effects or may prevent the advance stage of Alzheimer. Cluster analysis showed that the Medjool variety was separated from other varieties. Imported varieties from other regions of Iran (Zahedi, Piarom, Hallilehie and Mordasangh) were set into one group and the inherent varieties (Keroot, Mozafati) were set into another group. The results showed that the varieties from one geographical region had a close or relatively the same essential oil compositions.